The Influence of Claim Services on The Increase In Sales of Insurance Products At PT. Jasaraharja Putera - Budi Santosa; Boby Wiryawan Saputra (Green Publisher Indonesia, 2025)
This research investigates the influence of claim services on the sales of insurance products at PT. Jasaraharja Putera. The study focuses on three key variables: claim knowledge, claim process, and approved claims, analyzing their effects on customer repurchase intentions. A quantitative approach was employed, utilizing surveys to gather data from policyholders. Results indicate that all three variables positively impact customer loyalty and purchasing decisions. Among them, approved claims have the most significant effect, highlighting the importance of efficient claim processing and transparency in enhancing customer satisfaction. The findings provide valuable insights for the company to optimize its claim services and improve sales.